The systemic effects of the enriched environment on the conditioned fear reaction - Grigoryan, Grigory A. (Frontiers in Behavioral Neuroscience, 2023)
In this review, a hypothesis is proposed to explain the beneficial effect of an enriched environment (EE) on the conditioned fear reaction (CFR) from the perspective of a functional system of behavioral control. According to the hypothesis, the EE affects all behavioral act components, including the processing of sensory information, memory, motivational and reinforcing systems, and motor activities, which weakens the CFR. Animals raised in the EE have effects that are comparable to those of context (CTX) and CS pre-exposures at latent inhibition. An abundance of stimuli in the EE and constant contact with them provide the formation of CS-noUS and CTX-noUS connections that later, during CFR learning, slow down and diminish fear. The EE also contributes to faster processing of information and habituation to it. As a result, many stimuli in the context lose their significance, and subjects simply ignore them. And finally, the EE affects the motivational and reinforcing brain mechanisms, induces an impairment of search activity, and worsens memory consolidation, which leads to a reduction of CFR.